Efficacy and safety of concomitant use of proton pump inhibitors with aspirin-clopidogrel dual antiplatelet therapy in coronary heart disease: A systematic review and meta-analysis - Luo, Xiaofeng; Hou, Min; He, Shuangshuang; Yang, Xue; Zhang, Pan; Zhao, Yingxin; Xing, Haiyan (Frontiers in Pharmacology, 2023)
Background: Proton pump inhibitors (PPIs) are usually prescribed to prevent gastrointestinal (GI) complications in patients receiving dual antiplatelet therapy (DAPT). This systematic review and meta-analysis aimed to explore the efficacy and safety of the concomitant use of PPIs with aspirin-clopidogrel DAPT in patients with Coronary heart disease (CHD). Method: The PubMed, Embase, Cochrane Library, and Web of Science databases were searched from inception to August 2022 for eligible studies. The adjusted hazard ratios (HRs) and 95% confidence intervals (CIs) were calculated to evaluate the clinical outcomes. Subgroup analysis was conducted according to different PPI subtypes, populations, follow-up times and study types. This study was registered on PROSPERO (CRD42022332195). Results: A total of 173,508 patients from 18 studies [2 randomized controlled trials (RCTs), 3 post hoc analyses of RCTs, and 13 cohort studies] were included in this study. Pooled data revealed that coadministration of PPIs significantly increased the risk of major adverse cardiovascular events (MACEs) (HR=1.15, 95% CI=1.06-1.26, P=0.001) and reduced the risk of gastrointestinal (GI) complications (HR=0.44, 95% CI=0.30-0.64, P<0.0001). Subgroup analysis results showed that the esomeprazole users and patients with coronary stenting in the PPI group were associated with an increased risk of MACEs compared with the non-PPI group. The occurrence of MACEs in PPI users was more common than that in non-PPI users in long-term follow-up (≥ 12 months) studies and in the observational studies. There was no significant differences in the incidences of net clinical adverse events (NACEs), all-cause mortality, or cardiac death between the two groups. Conclusion: In patients with CHD, the concomitant use of PPIs with aspirin and clopidogrel was associated with a reduced risk of GI complications but could increase the rates of MACEs (particularly in patients receiving esomeprazole or with coronary stenting). There was no clear evidence of an association between PPI use and NACEs, all-cause mortality, or cardiac death. The results could have been affected by the follow-up time and study type. Further large-scale RCTs with long-term follow-up are needed.